PENGARUH MINAT DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL (Survei pada siswa kelas VIII MTs Swasta di Jakarta Timur) - Muslim, Ibnu Fiqhan (Universitas Indraprasta PGRI, 2019)
The purpose of this research is knowing how far effect of learning interest and learning motivation toward learning achievement, learning interest toward learning achievement, learning motivation toward learning achievement on social sciences subject. The Research method is using survey with correlation analysis and regression. Data about motivation study variabel and study motivation obtain by questionnairre which is prepared by researcher, that is measuring related two things above. Meanwhile data about studi achievement social subject obtain by direct test by researcher towards respondent. The results of the analysis state: (1) There is a significant influence together of interest and motivation to study on students' social studies learning achievement, this is evidenced by the Sig 0,000 <0,05 and F count = 66,487. While the magnitude of the contribution of interest and motivation to learn together on social studies learning achievement is shown by the coefficient of determination that is equal to 70% while the remaining 30% is due to other factors not examined. (2) There is a significant effect of learning interest on students' social studies learning outcomes. This is evidenced by the Sig 0,000 <0,05 and t count = 4,724. (3) There is a significant effect of students 'learning motivation on students' social studies learning outcomes. This is proven by the Sig 0,001 <0,05 and t count= 3,457.